Диагностика различных вариантов кардиомиопатий у детей. Новый взгляд на старую проблему (Часть 1) - Сухарева, Г.Э. (Таврический медико-биологический вестник, 2012)
У статті надана сучасна класифікація кардіоміопатій. Особлива увага приділена класифікації,
клініці і сімейним формам гіпертрофічної кардіоміопатії. Приведені власні спостереження за 16 дітьми
і їх найближчими родичами. The article presents a modern classification of cardiomiyopathy in children. A special attention is paid to
classification, clinic and family forms of hypertrophic cardiomiyopathy. The author’s own observations of 16
children and their next-of-kins are presented.